Analysis of Internal Control System of Trade Goods in Minang Motor Sport Stores Bengkulu City - Fatma Mulia; Oni Yulianti; Herlin Herlin (Penerbit Jurnal Indonesia, 2021)
The research objective was to determine the internal control system for merchandise inventory at the Minang Motor Sport Store, Bengkulu City. The data collection method in this study is to use the interview method. The analytical method used is descriptive analysis with a comparative type. The results showed that there was no match between Mulyadi's (2016: 488) theory and the conditions that occurred at the Bengkulu City Minang Motor Sport Shop for organizational elements, because according to Mulyadi's theory, physical inventory counting had to be carried out by a special committee formed apart from warehouse employees. . Meanwhile, what happened at the Minang Motor Sport Store, Bengkulu City, the physical count was carried out directly by the warehouse department. For the elements of the authorization system and the recording procedure of the conformity and discrepancy between Mulyadi's theory (2016: 488) and the Minang Motor Sport Store in Bengkulu City, the discrepancy is in the list of physical inventory count results signed by the chairman of the physical inventory counting committee and the recording of the physical inventory count results is recorded. the correctness of the physical counting card that has been verified. There is compatibility between Mulyadi's (2016: 488) theory with the Minang Motor Sport Store in Bengkulu City for elements of healthy practice, because at the Minang Motor Sport Store, Bengkulu City, the physical counting of merchandise inventory cards has been numbered sequentially, inventory checking has been carried out twice by the department. inventory counters and subsequently by inventory checkers.